Faktor yang Mempengaruhi Keputusan Petani Terhadap Hasil Panen Lada Putih di Kecamatan Simpang Teritip Kabupaten Bangka Barat - Pranoto, Yudi Sapta (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
This research aims to determine the factors that influence farmers decisions to harvest white pepper crops, which related to delay selling or direct selling.Â  Method of research Â used in this research was survey method, stratified random sampling was used on 60 respondents which categorized as large farmers and small farmers, and the method of Â analysis used logistic binary regression. The result showed that there was a difference between the large farmers and small farmersâ decisions. The tendency for large farmers do delay the selling and the tendency of small farmers as much as 57 percent do direct selling and 43 percent of farmers do delay selling. There are three variables that influence farmers decisions, namely the amount of production, price perception and consumption needs.